PENANGANAN DEPRESI GUNA MENJAGA KESEHATAN MENTAL PADA LANSIA DI GRIYA SEHAT BAHAGIA PALUR - Liss Dyah Dewi Arini; Saryadi Saryadi; Musta'in Musta'in; Dian Elizar; Arifatul Khoirunnisak (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2022)
Partner problems include that most of the elderly at Griya Sehat Bahagia experience depression and the treatment implemented by the Griya Sehat Bahagia Panti for elderly patients who experience depression is still very limited. So far, the treatment provided by the orphanage is manifested in several forms including self-talk, sedatives and closeness to Allah swt. The treatment given to the elderly aims to maintain mental health for the elderly so that they are all enthusiastic and motivated to live life at an age that is no longer productive. Mental health that is maintained will lead to a prosperous life both mentally, physically, spiritually and socially. The solution to the problems in partners is through counseling, training, monitoring, evaluation, providing skills and providing facilities that better support the lives of the elderly at Griya Sehat Bahagia. It is hoped that this community service activity can contribute to the restoration of the health of the elderly in the orphanage. From the socialization and also the training provided to the elderly at Griya Sehat Bahagia showed positive results, it was proven that the elderly were very enthusiastic about participating in activities and were more motivated than before. Keywords: elderly, depression, mental health, well-being